2009
DOI: 10.1243/09544054jem1654
|View full text |Cite
|
Sign up to set email alerts
|

Neural network approach for the selection of processing parameters of aluminium—iron composite preforms during cold upsetting

Abstract: The powder forging process of die forging, sintering, and upsetting is a convenient way of reducing or eliminating the porosity from traditional powder metallurgy products. Forging of metal powder enhances the demanding high-tensile, impact, and fatigue strength of powder metallurgy products. In this research, a demonstration system has been developed that employs a neural network for advising aluminium—iron composite compositions and optimum process settings with desired properties at an early stage in the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The formability of the powder metallurgy part is important in deciding if the compact will be shaped effectively or fracture occurs in the forming process. Poshal and Ganesan [2] predicted the values of deformation characteristics and formability factor using a proposed network model. They tested the model with experimental values and concluded that it is a promising technique and capable of predicting forming limit parameters together with production advice relating to many aspects of powder metallurgy including design, production and control.…”
Section: Introductionmentioning
confidence: 99%
“…The formability of the powder metallurgy part is important in deciding if the compact will be shaped effectively or fracture occurs in the forming process. Poshal and Ganesan [2] predicted the values of deformation characteristics and formability factor using a proposed network model. They tested the model with experimental values and concluded that it is a promising technique and capable of predicting forming limit parameters together with production advice relating to many aspects of powder metallurgy including design, production and control.…”
Section: Introductionmentioning
confidence: 99%
“…It is rapid, economical, and highvolume production method of porous materials, composite materials, refractory materials, and special duty alloys to be used in aircraft, automotive, and other manufacturing industries (Rosochowski et al 1998;Poshal and Ganesan 2010). Due to its optimal physical and mechanical properties, aluminum-copper composites have been widely applied in automobile and aerospace industries.…”
Section: Introductionmentioning
confidence: 99%
“…Powder metallurgy manufacturing technique is used to produce parts to close tolerance, intricate shapes, and near net shapes. It has proved to be cost effective of producing many parts such as porous materials, composite materials, refractory materials, and special high duty alloys [1][2][3] to be used in aircraft, automotive, and manufacturing industry. Further, powder metallurgy route is green manufacturing and energy efficient manufacturing compared to casting operation [4].…”
Section: Introductionmentioning
confidence: 99%